Kajian Karakteristik Pengeringan Kulit Kopi Arabika Menggunakan Pengering Mekanis Pada Berbagai Suhu - Yosika, Nur Ida Winni; Purbasari, Dian; Taruna, Iwan; Sutarsi, Sutarsi; Lestari, Ning Puji; Nofiyanti, Sri Handayani (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Arabica coffee husk is a by-product of coffee agroindustry that is generated in large quantities and has not been optimally utilized, particularly in coffee-producing areas such as Bondowoso Regency, Indonesia. Proper postharvest handling is required to reduce its moisture content in order to extend shelf life and enable further processing. This study aimed to investigate the drying characteristics of Arabica coffee husk using a hot air oven at different temperatures (40, 60, and 80°C) and to determine the most suitable mathematical drying model. Fresh coffee husk samples weighing 100 g were used for each drying treatment. The observed parameters included moisture content reduction, drying rate, and moisture ratio. Experimental drying data were fitted using Newton, Page, Henderson and Pabis, Logarithmic, and Midili models. The results showed that increasing drying temperature significantly accelerated moisture removal and increased the drying rate. Drying occurred predominantly in the falling rate period, indicating that internal moisture diffusion controlled the process. Among the evaluated models, the Logarithmic model consistently provided the highest coefficient of determination and the lowest fitting errors at all drying temperatures. These findings demonstrate that the Logarithmic model is the most appropriate for predicting the drying behavior of Arabica coffee husk dried using a convection oven. The results of this study are expected to support process design and decision-making in the management of coffee agroindustry, particularly for the utilization of coffee husk in Bondowoso.